Self-healing dynamically cross linked versatile polymer electrolyte: A novel approach towards high performance, flexible electrochromic devices. (10th October 2019) - Wang, Yi; Zheng, Rongzong; Luo, Junsheng; Malik, Haseeb Ashraf; Wan, Zhongquan; Jia, Chunyang; Weng, Xiaolong; Xie, Jianliang; Deng, Longjiang; Yao, Xiaojun
Abstract: Despite their wide spread implementation, electrochromic (EC) electrolytes based on polymethyl methacrylate, polyvinyl alcohol, polypropylene carbonate lack important properties like self-healing and stretchability which limits their applications for flexible/wearable electrochromic devices (ECD). Here, a dually-crosslinked self-healing polymeric electrolyte P(AA-VIm-VSN) has been synthesized containing acrylic acid (AA), 1-vinylimidazole (VIm) and vinyl hybrid silica nanoparticles (VSN) by copolymerizization process. The cross linking of VSN acts as a stress transfer center to eliminate energy and homogenize the polymer network, thus effectively reinforcing the polymer network under large strain. The dynamically cross-linked hydrogen bonds serve as "non-sacrificial bonds", which can be effectively recovered on breaking of polymeric network. The novel polymer electrolyte with excellent self-healing ability is important for the development of cost effective, durable and flexible ECD. The resultant gel showed excellent mechanical properties (tensile strength 11 kPa), and noticeable self-healing performance with healing efficiency of 90.5% within 20 min. Simultaneously, a type of hybrid ECD was fabricated containing the self-healing electrolyte with viologen EC materials and polyaniline film counter electrode. The hybrid devices showed well optical contrast (over 45%), fast switching time (2.0 s for coloring and 1.8 s for bleaching), coloration efficiency (406.96 cm 2 /C) and cyclic stability (>5000 cycles). Graphical abstract: A novel dual-crosslink polymeric electrolyte with self-healing property has been designed and synthesized, which possess excellent electrochromic performance on implementation as electrochromic devices (ECDs).Image 1 Highlights: A novel dual-crosslink polymeric electrolyte has been synthesized. The polymer electrolyte displays excellent mechanical properties and self-healing performance. The gel electrolyte has great potential for ECDs. The hybrid ECDs achieve excellent electrochromic performance.